(untitled) (The Peerian Journal, 2022)
In this accelerating globe, the most optimal way to increase the effectiveness of general education is to organize lessons using interactive methods. So, what are interactive methods? What didactic possibilities do they have? What results can be guaranteed by the appropriate and purposeful use of interactive methods in the process of mother tongue education? We will try to answer these questions in this article.